(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the role of laparoscopic technologies, one of the most promising areas of application for these purposes, and discusses the technical and clinical achievements of minimally invasive intervention compared to traditional laparotomy. The article scientifically substantiates the importance of laparoscopy in improving the quality of life of patients.